Effectiveness of inoculation of in vitro-grown potato microplants with rhizosphere bacteria of the genus Azospirillum - Kargapolova, Kristina Yu; Burygin, Gennady L.; Tkachenko, Oksana V.; Evseeva, Nina V.; Pukhalskiy, Yan V.; Belimov, Andrey A. (Plant cell, tissue and organ culture, 2020)
Key message The response of potato microplants to Azospirillum inoculation is highly variable both in vitro and ex vitro. Plant inoculation with plant-growth-promoting rhizobacteria (PGPR) is widely used to increase the effectiveness of clonal micropropagation. Azospirillum rhizobacteria are model subjects to investigate associative plant–microbe interactions. Here we show that most Azospirillum strains cannot utilize sucrose as the sole carbon source and that their use to inoculate in vitro-grown plants does not lead to bacterial growth in the culture medium. Of the eleven surveyed strains, seven gave a significant increase in at least one growth variable of in vitro-grown potato ( Solanum tuberosum L. cv. Nevsky) microplants. Inoculation with six strains led to better survival of the microplants in soil. Only with three strains ( A. brasilense Sp245, SR80, and A. halopraeferens Au4 T ) did inoculation in vitro significantly promote plant growth ex vitro. The inoculation results were correlated with the biochemical activity of the strains. Indole-3-acetic acid production ranged from 3.74 μg ml −1 with A. brasilense S27 to 87.3 μg ml −1 with A. brasilense Sp245. Active indole-3-acetic acid producers, but not nitrogen fixers, were better plant-growth-promoters. Inoculation in vitro with A. brasilense strains Sp245 and SR80 can be recommended for increasing the effectiveness of clonal micropropagation of potato.